The Framed World : tourism, tourists and photography - Picard, David; Robinson, Mike (USA; Routledge, 2009)
Photographs create visual narratives of experiences, places, peoples and objects that collectively and individually comprise the tourist gaze. Photography is acknowledged as having an important role in the determining of places and spaces, the construction and re-construction of identities, and the invention and re-invention of histories.
English
Keywords: G154.9-155.8 Travel and state. Tourism; Tourism industry